Religious Digital Resilience: A Conceptual Model for Strengthening Religious Moderation among Generation Z through Islamic Education - Muharleni; Neni Sriwahyuni; Mellia Ristika; Yeni Sulastri (Islamic Studies and Education Journal, 2026)
The rapid growth of social media has fundamentally transformed how Generation Z acquires, constructs, and disseminates religious knowledge. On the one hand, social media provides significant opportunities to promote religious moderation through digital da'wah, educational content, and interactive learning environments. On the other hand, algorithm-driven platforms, information overload, and weak source verification have intensified the spread of religious extremism, intolerance, and digital misinformation. These challenges require Islamic education to move beyond the transmission of religious knowledge by strengthening digital literacy, critical thinking, and digital resilience among learners. This study aims to analyze Islamic education strategies for strengthening religious moderation on social media to address digital radicalism and misinformation among Generation Z. The study employed a conceptual review method through a critical synthesis of peer-reviewed journal articles, academic books, and policy documents related to religious moderation, Islamic education, digital literacy, and digital radicalization. The findings indicate that strengthening religious moderation requires the integration of four interconnected components: religious moderation values, digital literacy, adaptive Islamic pedagogy, and a collaborative ecosystem involving schools, families, religious organizations, government institutions, and digital platforms. Based on this synthesis, the study proposes the Religious Digital Resilience Model as its primary conceptual contribution, explaining how these components collectively develop Generation Z's capacity to access, verify, evaluate, and disseminate religious information critically, ethically, and responsibly. The proposed model extends the discourse on religious moderation from a normative framework toward a transformative educational approach integrating theological, pedagogical, and digital dimensions.